2021
DOI: 10.1093/ppmgov/gvaa026
|View full text |Cite
|
Sign up to set email alerts
|

Systematically Reviewing American Law and Public Administration: A Call for Dialogue and Theory Building

Abstract: Many of the world’s most pressing issues lay at the intersection of law and public administration. However, many have long lamented the relatively weak and atomized state of law and public administration scholarship. In this article, we use bibliometric and content analyses to systematically assess the last 20 years of literature, exploring the extent to which law and public administration have developed as a coherent paradigm. In short, we provide a contemporary assessment of the past assertion that “public a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 70 publications
1
3
0
Order By: Relevance
“…However, we do find support for an insularity of public administration with regard to the third of the founding disciplines, that is, law (Rosenbloom, 1983). The divergent evolution of public administration and administrative law has recently been analyzed (Osorio et al, 2021) and our study echoes these findings. It should be noted here that our method might underestimate the influence of law because in legal scholarship, publishing in journals does not play the same pivotal role than in many other fields.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…However, we do find support for an insularity of public administration with regard to the third of the founding disciplines, that is, law (Rosenbloom, 1983). The divergent evolution of public administration and administrative law has recently been analyzed (Osorio et al, 2021) and our study echoes these findings. It should be noted here that our method might underestimate the influence of law because in legal scholarship, publishing in journals does not play the same pivotal role than in many other fields.…”
Section: Resultssupporting
confidence: 88%
“…Remarkably, some of these initial topics retained their relevance for a long time. The thematic cluster on administrative law (#16), for example, was still referenced in the literature on public service contracting (#51) in the NPM era, making a case for a dialog between public administration and law (Osorio et al, 2021). In the later periods, few topics attracted a clear majority of citations.…”
Section: Evolution Of Pamentioning
confidence: 99%
“…The three disciplines that have been recognized as foundational to the study of PA are political science, management, and law (Rosenbloom, 1983; Wright, 2011). To the regret of many scholars (Osorio et al, 2021), the roots in and dialogue with legal studies seem to have been lost. In turn, many other disciplines have gained influence, most notably economics, sociology, and psychology (Hustedt et al, 2020; Vogel & Hattke, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Several previous studies have examined law journals and found characteristics that are related to the country or region where the journal is published [7][8][9][10][11][12], while other studies have attempted to identify interdisciplinary characteristics of law journals. These include psychology and law [13], psychiatry and law [14], library and information science and law [15], and public administration and law [16]. Focusing on a particular type of law journal was also a common approach to finding characteristics of law journals.…”
Section: Related Studiesmentioning
confidence: 99%